ECONOMIC EMPOWERMENT AND FINANCIAL INCLUSION OF POOR PEOPLE IN INDIA THROUGH MICROFINANCE - Jana, Subrata; kali, Sukhen (IJRDO - Journal of Social Science and Humanities Research, 2017)
In spite of sincere effort by the Central and State Governments to improve the financial and social conditions of the poor people, especially in the rural India through various poverty alleviation programmes, the outcomes has far from satisfactory level. Self Help Groups emerges as one of the major tool in promoting financial inclusion for inclusive growth in India. Formal banking sector also ignored the poor due to risk involved in lending to poor. On this backdrop NABARD backed Self Help Group bank linkage is considered as best alternative to reach the rural poor. After 1990s microfinance has picked its momentum and now it is the largest microfinance movement in India. The main aim of NRLM is to reduce poverty by enabling the poor house holders.. The basic idea behind this programme is organize the poor in to Self groups and make them capable for self employment. This study attempts to review the spread of credit linkages between self-help groups (SHGs) with special reference to the women SHGs and NRLM programme.